2020
DOI: 10.1115/1.4047323
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Predictive Model for Downhole Pressure Surges During Tripping Operations Using Power Law Drilling Fluids

Abstract: Abstract Surge/swab pressure is a crucial parameter that provokes well-control problems such as fluid loss, fractured formations, fluid influx, and kick. Thus, a precise estimation of differential pressure is required to evade any unforeseen drilling difficulties. The existing predictive models are based on narrow-slot approximation methods and consider the effect of drilling string axial movement on downhole pressure surges. However, it ignores the impact on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…( 14) and Eqs. (15), the 3D nonlinear coupling vibration governing equations of the drill string system can be obtained and written as:…”
Section: Governing Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…( 14) and Eqs. (15), the 3D nonlinear coupling vibration governing equations of the drill string system can be obtained and written as:…”
Section: Governing Equationmentioning
confidence: 99%
“…It was found that drill string eccentricity reduced the frictional pressure loss more significantly under high diameter ratio conditions [14]. Krishna et al studied the influence of the axial movement of the drill string on downhole pressure fluctuation during the tripping of the drill string and found that with the increase of the tripping speed, the diameter ratio had a significant influence on the differential pressure [15]. Joshi et al estimated the influence of eccentricity on annular pressure loss through numerical simulation, and the results showed that the pressure loss was directly related to the inlet velocity and rotational speed, and the pressure loss of concentric tube was smaller than that of fully eccentric tube [16].…”
Section: Introductionmentioning
confidence: 99%